Perilaku Pengasuhan Orang Tua dan Bayang-Bayang Depresi Mahasiswa - Arifiati, Retna Febri; Wahyuni, Endang Sri (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: The current study examined the relationship between perceptions of parenting styles and depressive symptoms in college students. Depression is a mood disorder characterized by major symptoms of depressed mood, loss of interest, and loss of energy, characterized by fatigue. Depression can be a serious health condition, as it can lead to suicide. Suicide is the second leading cause of death in 15-29 year olds. Objectives: The purpose of this study was to determine the relationship between perceptions of parenting styles and depressive symptoms in Occupational Therapy students. Methods: The research method used was a quantitative research method using a scale of perceptions of parenting styles (Parental Authority Questionnaire Revised-PAQ-R) and a depression scale using the Hamilton Depression Rating Scale (HDRS). The sample size was 200 people taken using incidental sampling technique. The data analysis of this study used a product moment correlation analysis technique with the help of Statistical Product and Service Solution (SPSS) 20.0 for Windows. Results: The results of the analysis produced a value of r = 0.247 which means there is a significant positive relationship between the variable of perception of parenting patterns (authoritarian) with symptoms of depression with a value of p = 0.000 (p <0.05) with an effective contribution of 6.1%. Conclusion: Based on the results of the study, it can be concluded that the higher the perception of parenting patterns (authoritarian) the higher the symptoms of depression, conversely, if the lower the perception of parenting patterns (authoritarian) the lower the symptoms of depression. From these findings support that the perception of parenting (authoritarian) will be related to anxiety and symptoms of depression. Keywords: Perception of Parenting Patterns, Depressive Symptoms, Students, Adults.